Thomas' Calculus 13th Edition

Published by Pearson
ISBN 10: 0-32187-896-5
ISBN 13: 978-0-32187-896-0

Chapter 3: Derivatives - Section 3.3 Differentiation Rules - Exercises 3.3 - Page 125: 11


First Derivative: $r'=\frac{-2}{3s^{3}}+\frac{5}{2s^{2}}$ Second Derivative: $r''=\frac{2}{s^{4}}-\frac{5}{s^{3}}$

Work Step by Step

Using the Power Rule: First Derivative: $r=\frac{1}{3s^{2}}-\frac{5}{2s}$ $r'=(-2)(\frac{1}{3})s^{-2-1}-(-1)(\frac{5}{2})s^{-1-1}$ $r'=\frac{-2}{3}s^{-3}+\frac{5}{2}s^{-2}$ $r'=\frac{-2}{3s^{3}}+\frac{5}{2s^{2}}$ Second Derivative: $r'=\frac{-2}{3}s^{-3}+\frac{5}{2}s^{-2}$ $r''=(-3)\frac{-2}{3}s^{-3-1}+(-2)\frac{5}{2}s^{-2-1}$ $r''=2s^{-4}-5s^{-3}$ $r''=\frac{2}{s^{4}}-\frac{5}{s^{3}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.